Challenges to children's health in Primary Care: integrative literature review (Research, Society and Development, 2021)
Introduction: Maternal and child health policies have been successful over the years. The child population represents 26% of the world population, while in Brazil, this population reaches 21.10%. It is worth highlighting the role of Community Health Agents in improving maternal and child health outcomes, both in low- and middle-income countries and in less favored communities Objective: To identify, in the literature, the main difficulties encountered by health professionals in childcare for children in primary care. Material and methods: An integrative literature review on childcare was conducted with a focus on the quality of care in primary care. Publications were searched from 2015 to 2019 at Medline, PubMed and SciElo databases. Prioritizing publications from 2017 to 2019 for analysis, they were separated into groups a to G according to their research designs and levels of scientific evidence.. Results: The findings corroborated the analysis of how primary care is for children. In a specific way, childcare still lacks well-trained professionals with a desire to deal with the pediatric public. It is possible to notice the lack of public incentives and good management in primary health units so that the services are offered satisfactorily. Conclusion: Efforts have been concentrated to ensure the best care in childcare in basic health units. However, there is still a lack of interest, lack of commitment to children, poor public management and reduced financial incentives.